Simultaneous determination of related substances of oxytetracycline in pharmaceutical semi-solid form by HPLC method - Violeta Giugiu (Medicamentul Veterinar, 2013)
Simultaneous determination of oxytetracycline, 4-epioxytetracycline, alpha-apooxytetracycline, tetracycline, beta-apooxytetracycline on C18 columns has been accomplished using a high performance liquid chromatographic method with UV detection. Separation was achieved on a Hypersil BDS RP-C18 column with a mobile phase consisted of acetonitrile-methanol-80 mM dipotassium phosphate pH 7,5 at a flow rate of 0,7 mL min-1. Absorbance measurements were held at 254 nm.